Southwest Pacific Ocean response to a warming world: Using Mg/Ca, Zn/Ca, and Mn/Ca in foraminifera to track surface ocean water masses during the last deglaciation - Marr, Julene P.; Carter, Lionel; Bostock, Helen C.; Bolton, Annette; Smith, Euan (Paleoceanography, 2013)
In situ measurements of Mg/Ca, Zn/Ca, Mn/Ca, and Ba/Ca in Globigerinoides bulloides and Globigerina ruber from southwest Pacific core top sites and plankton tow are reported and their potential as paleoproxies is explored. The modern samples cover 20 degrees of latitude from 34 degrees S to 54 degrees S, 7-19 degrees C water temperature, and variable influence of subantarctic (SAW) and subtropical (STW) surface waters. Trace element signatures recorded in core top and plankton tow planktic foraminifera are examined in the context of the chemistry and nutrient profiles of their modern water masses. Our observations suggest that Zn/Ca and Mn/Ca may have the potential to trace SAW and STW. Intraspecies and interspecies offsets identified by in situ measurements of Mg/Ca and Zn/Ca indicate that these ratios may also record changes in thermal and nutrient stratification in the upper ocean. We apply these potential proxies to fossilized foraminifera from the high-resolution core MD97 2121. At the Last Glacial Maximum, surface water Mg/Ca temperature estimates indicate that temperatures were approximately 6-7 degrees C lower than those of the present, accompanied by low levels of Mn/Ca and Zn/Ca and minimal thermal and nutrient stratification. This is consistent with regional dominance of SAW and reduced STW inflow associated with a reduced South Pacific Gyre (SPG). Upper ocean thermal and nutrient stratification collapsed during the Antarctic Cold Reversal, before poleward migration of the zonal winds and ocean fronts invigorated the SPG and increased STW inflow in the early Holocene. Together with reduced winds, this favored a stratified upper ocean from circa 10ka to the present.